THE EFFECTIVENESS OF RATER TRAINING IN IMPROVING THE SELF-ASSESSMENT INTRA-RATER RELIABILITY OF ENGLISH SPEAKING PERFORMANCE (Universitas Negeri Semarang, 2011)
This quantitative study is an attempt to estimate the intra-rater reliability ofstudent self-assessment of their speaking performances and to find outwhether there is significant difference between the self-assessment intra-raterreliability of speaking performance without training and that of with training.The rater training used is adapted from the model developed by Herman,Aschbacher and Winters (1992). This study which employed equivalent timesamplesdesign collected data by asking 45 students to conduct selfassessmenton their six speaking performances. It was found that the range ofrs was 0.611 to 0.752 which means the consistency within students inassessing their own speaking performance was moderate high to high. Theintra-rater reliability of the self assessment after the treatments is higher thanthat of other experience being available in the absence of the treatment. It isconcluded that rater training improves the intra-rater reliability. Therefore, itis suggested to train the students on how to assess before employing selfassessmentin speaking instructions.